The Determinants of Monetary Policy in Malaysia: Impact on Economic Activity - Mohd Yusoff, Zetty Zahureen; Mohd Masdek, Nik Rozila Nik; Osman, Adibah Alawiyah; Azahar, Ariq Syazwan; Husin, Norhusniyati; Ghul, Zahirah Hamid (Information Management and Business Review, 2024)
The overnight interbank rate is a key tool for central banks to influence economic activity and maintain financial stability. It represents the rate at which banks lend and borrow short-term funds from one another, often overnight, and plays a crucial role in monetary policy transmission. Changes in this rate can affect borrowing costs and credit availability, which in turn impacts consumption, investment, and economic activity. Bank Negara Malaysia (2021) highlights that overnight transactions in the interbank market operate alongside the Kuala Lumpur Interbank Offered Rate (KLIBOR). This study analyzes time series data from 1991 to 2021 to identify relationships between the overnight interbank rate and macroeconomic variables using the ordinary least square (OLS) method. The analysis focuses on unemployment (UR), domestic private credit (DGR), gross domestic product (GDP), foreign exchange reserves (FER), and inflation (I), with data sourced from the World Bank and the Federal Reserve Bank (FRED). The results show that unemployment and inflation significantly impact monetary policy. High unemployment suggests underused resources, often prompting lower interest rates to stimulate investment and economic growth. In contrast, rising inflation typically leads central banks to increase interest rates to slow spending, while falling inflation may result in rate cuts to spur economic activity.